2021
DOI: 10.3390/ma14154195
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Induced Catalyst Support Defects for the Photothermal Methanation of Carbon Dioxide

Abstract: The presence of defects in a catalyst support is known to benefit catalytic activity. In this work, a He-plasma treatment-based strategy for introducing and stabilising defects on a Ni/TiO2 catalyst for photothermal CO2 hydrogenation was established. The impact of pretreatment step sequence—which comprised He-plasma treatment and reduction/passivation—on defect generation and stabilisation within the support was evaluated. Characterisation of the Ni/TiO2 catalysts indicated that defects created in the TiO2 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…To increase the performance of another nickel CO 2 methanation catalyst, Scott, Lovell and co-workers utilized a plasma treatment to create a defective titania support. [146] Nickel nanoparticles were subsequently deposited on the support, and different combinations of reduction steps and plasma passivation treatments were studied. The authors reported that the plasma treatment resulted in extra oxygen vacancies, which increased the interaction between CO 2 and the support, leading to improved performance of the catalytic system.…”
Section: Weakly Plasmonic Metal Nanoparticle Based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the performance of another nickel CO 2 methanation catalyst, Scott, Lovell and co-workers utilized a plasma treatment to create a defective titania support. [146] Nickel nanoparticles were subsequently deposited on the support, and different combinations of reduction steps and plasma passivation treatments were studied. The authors reported that the plasma treatment resulted in extra oxygen vacancies, which increased the interaction between CO 2 and the support, leading to improved performance of the catalytic system.…”
Section: Weakly Plasmonic Metal Nanoparticle Based Catalystsmentioning
confidence: 99%
“…To increase the performance of another nickel CO 2 methanation catalyst, Scott, Lovell and co‐workers utilized a plasma treatment to create a defective titania support [146] . Nickel nanoparticles were subsequently deposited on the support, and different combinations of reduction steps and plasma passivation treatments were studied.…”
Section: Catalysts For Solar‐driven Co2 Reductionmentioning
confidence: 99%
“…(c and d) Influence of Ni/TiO 2 catalyst pretreatment on (c) CO 2 conversion and (d) methane selectivity during decoupled photo and thermal CO 2 methanation in a continuous flow reactor system. Reproduced with permission from ref . Copyright 2021 The Author(s).…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…For example, in the initial stage of plasma treatment, the time of the catalyst (P-R)Ni/TiO 2 (obtained by He-plasma treatment and then reduction/ passivation) to reach the maximum CH 4 generation amount in the full-spectrum batch cycle reactor system was shorter compared with the catalyst (R-P)Ni/TiO 2 (obtained by first reduction/passivation and then He-plasma treatment), as shown in Figure 9a−d. 116 Research indicated that the defects produced by plasma treatment of TiO 2 support could be stabilized by the reduction/passivation process, while reduction/passivation produced resistance to the formation of defects in plasma treatment. In addition, catalysts derived from precursors with MOF have also attracted great attention.…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…However, the consumption of fossil fuels has led to one of the greatest conflicts between reserves and demand in this century [3,4]. Transforming relatively abundant energy resources into high value-added energy resources through sustainable approaches has been considered as a powerful way to alleviate the above contradiction [5][6][7][8]. Among them, methane, as the main component of natural gas and shale gas with abundant reserves, has become the focus of the above research [9][10][11].…”
Section: Introductionmentioning
confidence: 99%